2006
DOI: 10.1002/art.21675
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic inflammation, not its treatment, with increased lymphoma risk in rheumatoid arthritis

Abstract: Objective. Chronic inflammatory conditions such as rheumatoid arthritis (RA) have been associated with malignant lymphomas. This study was undertaken to investigate which patients are at highest risk, and whether antirheumatic treatment is hazardous or protective.Methods. We performed a matched case-control study of 378 consecutive Swedish RA patients in whom malignant lymphoma occurred between 1964 and 1995 (from a population-based RA cohort of 74,651 RA patients), and 378 controls. Information on disease cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
573
5
43

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 796 publications
(650 citation statements)
references
References 30 publications
29
573
5
43
Order By: Relevance
“…The following parameters were examined in the MTX non-LPD group and the MTX-LPD group: 1) age at RA onset, 2) RA disease duration, 3) joint destruction estimated using the Steinbrocker classification, 4) medications other than MTX, 5) corticosteroid treatment, 6) treatment with biologic agents, 7) age at MTX initiation, 8) mean MTX dose, 9) total MTX dose, and 10) complications of Sjögren's syndrome. When the relative risk of LPD including malignant lymphoma was estimated as being 4.0, in agreement with Baecklund et al (11), and the number of case-control sets was 20, the relative power for 4 controls per case was estimated as being approximately 62% (12). A comparison of parameters between the 2 groups was undertaken using an unpaired t-test, chisquare test, covariance analysis, and logistic regression analysis with StatView, version 5.0 (SAS).…”
Section: Epidemiologysupporting
confidence: 87%
See 2 more Smart Citations
“…The following parameters were examined in the MTX non-LPD group and the MTX-LPD group: 1) age at RA onset, 2) RA disease duration, 3) joint destruction estimated using the Steinbrocker classification, 4) medications other than MTX, 5) corticosteroid treatment, 6) treatment with biologic agents, 7) age at MTX initiation, 8) mean MTX dose, 9) total MTX dose, and 10) complications of Sjögren's syndrome. When the relative risk of LPD including malignant lymphoma was estimated as being 4.0, in agreement with Baecklund et al (11), and the number of case-control sets was 20, the relative power for 4 controls per case was estimated as being approximately 62% (12). A comparison of parameters between the 2 groups was undertaken using an unpaired t-test, chisquare test, covariance analysis, and logistic regression analysis with StatView, version 5.0 (SAS).…”
Section: Epidemiologysupporting
confidence: 87%
“…The frequencies of MTX-LPD in our patients and the reports from other countries were 0.5% and 0.05-0.3%, respectively, which are quite similar (5,11). However, the mean MTX dose showed a significant difference between the LPD and the non-LPD group in our study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A reappraisal of RA disease manifestations over the last decade has emphasized the expanding spectrum of the rheumatoid syndrome, which now includes accelerated cardiovascular disease as well as increased susceptibility to lymphoma and infection (1)(2)(3). Although the broad use of immunosuppressants makes it difficult to distinguish between iatrogenic and disease-intrinsic pathogenic factors, it is clear that the overall immunocompetence of RA patients is compromised (4).…”
mentioning
confidence: 99%
“…This question of whether lymphoma in RA may result from insufficient or too-aggressive immunosuppressive therapy has been addressed in an elegant study by Baecklund and colleagues, reported elsewhere in this issue of Arthritis & Rheumatism (14). By making use of unique patient and tissue registries in Sweden and tracking large cohorts of RA patients over decades, those researchers identified 378 consecutive cases with RA and subsequent malignant lymphoma and compared them with 378 control patients from a population-based cohort of 74,651 Swedes followed up for the diagnosis of RA.…”
mentioning
confidence: 99%